2020
DOI: 10.1152/ajpgi.00340.2019
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific lymphatics play distinct roles in regulating HDL trafficking and composition

Abstract: Recently, peripheral lymphatic vessels were found to transport high-density lipoprotein (HDL) from interstitial tissues to the blood circulation during reverse cholesterol transport. This function is thought to be critical to the clearance of cholesterol from atherosclerotic plaques. The role of organ-specific lymphatics in modulating HDL transport and composition is, however, incompletely understood. This study aimed to 1) determine the contribution of the lymphatics draining the intestine and liver (which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…We recently reported that lymph HDLs, which vary with the collection site, are less stable than plasma HDL and are modified during passage through lymphatics. 27 The thoracic lymph HDLs here were spherical particles 8−20 nm in diameter. This is unlike published reports that have observed traces of discoidal particles in rat mesenteric lymph 24,25 and human leg lymph HDL fractions.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We recently reported that lymph HDLs, which vary with the collection site, are less stable than plasma HDL and are modified during passage through lymphatics. 27 The thoracic lymph HDLs here were spherical particles 8−20 nm in diameter. This is unlike published reports that have observed traces of discoidal particles in rat mesenteric lymph 24,25 and human leg lymph HDL fractions.…”
Section: ■ Resultsmentioning
confidence: 99%
“…HDL 2 may be too large to enter the fenestrated blood vessels that drain to the portal blood, such that only intestine-derived HDL 3 gains efficient access. Consistent with this possibility, mesenteric lymph is relatively deficient in the smaller HDL 3 particles while relatively enriched in HDL 2 ( 35 ).…”
Section: Discussionmentioning
confidence: 75%
“…Recently, particular attention has been paid to RCT and atherosclerosis development, as well as their relation with arterial lymphatic drainage. However, the role of organspecific lymphatics in modulating HDL transport and composition is incompletely understood [44]. Especially, the lymphatic origin and flow vary among tissues, e.g., lymphatic drainage in the skin, intestine, liver and peritoneal cavity, which may further reflect the importance of lymphatics in RCT and atherosclerosis.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Initial lymphatics draining the peritoneal submesothelial layer have favorable absorption of lipophilic and unionized compounds [47]. The study by using nonfasted rats has demonstrated that the lipoproteins in lymph are organ specific in composition, and the intestine and liver appear to be the main source of HDL that is modified during transport from the mesenteric and hepatic lymphatics to the thoracic duct [44]. The lymph lipoprotein remodeling may indicate an alteration of its biological properties and potentially impact on the development of atherosclerosis.…”
Section: Atherosclerosismentioning
confidence: 99%